Environmental risk factors of Parkinson’s disease: a scoping review - Faeiz Syezri Adzmin Jaafar; Azimatun Noor Aizuddin; Norfazilah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Risk factors for Parkinson’s disease (PD) fall into three broad categories, namely environmental, genetic, and lifestyle factors. Identifying environmental factors that increase the risk of PD would allow these exposures to be reduced and the prevent disease while facilitating experimental investigation of mechanisms and intervention options. Thus, the aim of this review was to summarise the current evidence on the role of environmental factors in the development of PD. All original articles published between 2018 and 2022 and written in English were searched from three databases, i.e., PubMed, Scopus Web of Science (WoS), using combination of primary keyword (PD and its MeSH and synonyms), and two secondary keywords; (“environment*”) and risk (factor*). After a thorough screening process, 19 articles were included in this scoping review. The environmental risk factors examined in the included studies fell into five categories: a) pesticide exposure, b) heavy metals and organic solvent exposure, c) drug abuse and d) air pollution and e) source of water. In summary, PD is a complex neurological disorder for which there are several environmental risk factors involved. Identifying and reducing exposure to these environmental factors could have a significant impact on the future occurrence of the disease.